2004
DOI: 10.1016/s0213-9111(04)71848-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparación entre los niños de etnia gitana e inmigrantes extranjeros ingresados en centros de protección por maltrato

Abstract: Identifying the differences between these two groups of maltreated children could be useful for professionals working in the community social services in charge of developing intervention strategies for the prevention and early detection of maltreatment, as well as for professionals in charge of the health of these children during their stay in a protection center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…OlivánGonzalvo (2004a, 2004b) compared Spanish Roma children ( n = 83) to foreign children ( n = 105) in Spanish protection centres in detail. His results suggested that Spanish Roma children were statistically significantly more neglected physically and emotionally than foreign children.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…OlivánGonzalvo (2004a, 2004b) compared Spanish Roma children ( n = 83) to foreign children ( n = 105) in Spanish protection centres in detail. His results suggested that Spanish Roma children were statistically significantly more neglected physically and emotionally than foreign children.…”
Section: Resultsmentioning
confidence: 99%
“…Although qualitative research is essential to obtain an understanding of the contexts, vulnerabilities and needs of the people in a specific context, quantitative research is still needed to generalise the data to broader contexts, as well as to replicate the former studies, for example, those of Kisfalusi et al (2020), Kolarcik et al (2016), Oliván Gonzalvo (2004a, 2004b), Tokuç et al (2010) and Vazsonyi et al (2016). We believe that for both the study of offending and victimisation among the Roma, and most importantly, its comparison with the general population, a pragmatic solution would be to include a question about the participants’ ethnicity in the crime victims’ surveys as well as in the self-reported delinquency studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations